Exchange Rate Volatility and Productivity Growth: The Role of Financial Development - Philippe Aghion; Philippe Bacchetta; Romain Ranciere; Kenneth Rogoff (Swiss National Bank, Study Center Gerzensee, 2006)
This paper offers empirical evidence that real exchange rate volatility can have a signi.cant impact on the long-term rate of productivity growth, but the effect depends critically on a country's level of financial development. For countries with relatively low levels of financial development, exchange rate volatility generally reduces growth, whereas for financially advanced countries, there is no significant effect. Our empirical analysis is based on an 83 country data set spanning the years 1960-2000; our results appear robust to time window, alternative measures of financial development and exchange rate volatility, and outliers. We also offer a simple monetary growth model in which real exchange rate uncertainty exacerbates the negative investment effects of domestic credit market constraints. Our approach delivers results that are in striking contrast to the vast existing empirical exchange rate literature, which largely finds the effects of exchange rate volatility on real activity to be relatively small and insignificant.
Keywords: 330; Wechselkurs; Volatilität; Produktivität; Wirtschaftswachstum; Finanzmarkt; Schätzung